Arts-Based Methods in Education - A Global Perspective - Chemi, Tatiana; Du, Xiangyun (Arts-Based Methods in Education Around the World, 2018)
This chapter introduces the field of arts-based methods in education with a general theoretical perspective, reviewing the journey of learning in connection to the arts, and the contribution of the arts to societies from an educational perspective. Also presented is the rationale and structure of the book, as well as a summary of the following chapters. This chapter introduces the field of arts-based methods in education with a general theoretical perspective, reviewing the journey of learning in connection to the arts, and the contribution of the arts to societies from an educational perspective. The constructivist approach to the child's self-development and self-expression has had a great impact on how the teacher and educator think about art, culture, and aesthetics as active learning tools in the classroom. The value of the arts is measured in economic terms and put up against a monolithic practice of education. The neurosciences reveal the workings of the artistic brain and how emotions are fundamental to learning. Human beings are the only animals capable of and interested in cognitive abstractions such as symbolising, aesthetic elaboration, imagination, and innovation.